Digital Transformation in Public Sector: Case Study on Licensing Services to Start a Business in Pekalongan City - Satria Aji Imawan; Muhammad Syafiq; Sofiyah; Agus Heruanto Hadna; Achmad Djunaedi (Global Writing Academica Researching & Publishing, 2023)
This study had two formulated objectives. First, this study wanted to evaluate the achievements of the digital transformation process in licensing services to start a business in Pekalongan City, Central Java, Indonesia. Second, this study also expected to identify the factors that influenced the achievement of the digital transformation process in licensing services to start a business in Pekalongan City. This study used qualitative approach to answer the problem formulation through a case study. Data and information were analyzed using chronological time series analysis techniques. The informants of this research were selected through the snowball method. The results of data and information analysis showed that Pekalongan City was at the e-government stage. Three reasons that justified that the achievement was not at the digital government stage. First, users or citizens had not voiced demand in the digital transformation process. Second, the transformation of internal work processes had not yet taken place. Third, there had not been a shared database sharing process between related agencies either within the Pekalongan City government environment or with central government agencies. The analysis also showed that five factors that influenced the process of digital transformation in licensing services to start a business in Pekalongan City, those were: strategic factors, digital cultural factors, leadership factors, human resource capacity factors, and the role factor of central government organizations.